2013
DOI: 10.1016/j.jacc.2013.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obstructive Sleep Apnea Reduces the Risk of Atrial Fibrillation Recurrence After Catheter Ablation

Abstract: CPAP is an important therapy in OSA patients undergoing PVI that improves arrhythmia free survival. PVI offers limited value to OSA patients not treated with CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
202
0
23

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(242 citation statements)
references
References 24 publications
8
202
0
23
Order By: Relevance
“…Obturacyjny bezdech senny nasila zmiany ciśnienia wewnątrz klatki piersiowej, które same oraz za pośrednictwem aktywacji nerwu błędnego mogą prowadzić do skrócenia potencjału czynnościowego w przedsionkach i wywoływać AF. Redukcja czynników ryzyka oraz wentylacja z ciągłym dodatnim ciśnieniem w drogach oddechowych mogą ograniczać nawroty AF [308][309][310][311][312]. Wydaje się rozsąd-nym rozważanie przesiewowego wykrywania obturacyjnego bezdechu sennego u pacjentów z AF i obciążonych czynnikami ryzyka.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…Obturacyjny bezdech senny nasila zmiany ciśnienia wewnątrz klatki piersiowej, które same oraz za pośrednictwem aktywacji nerwu błędnego mogą prowadzić do skrócenia potencjału czynnościowego w przedsionkach i wywoływać AF. Redukcja czynników ryzyka oraz wentylacja z ciągłym dodatnim ciśnieniem w drogach oddechowych mogą ograniczać nawroty AF [308][309][310][311][312]. Wydaje się rozsąd-nym rozważanie przesiewowego wykrywania obturacyjnego bezdechu sennego u pacjentów z AF i obciążonych czynnikami ryzyka.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…311 Treatment of OSA with CPAP, however, appears to favorably impact AF management, regardless of the rhythm control strategy adopted. 315,316 …”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…283,289,290,291,316,317,318,319 Although OSA has been associated with poorer outcomes, CPAP appears to attenuate the deleterious impact of OSA. Pooled analysis suggests that although OSA increases the risk of AF recurrence following ablation (RR 1.31; 95% CI 1.16–1.48; P <.001), CPAP therapy improves ablation success to rates comparable with non-OSA populations (RR 1.25; 95% CI 0.77–2.03; P = .37).…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
See 1 more Smart Citation
“…200 Observational studies have demonstrated a significantly lower risk of recurrent AF in patients with treated compared with untreated OSA. 481 …”
Section: Age and Atrial Fibrillation Ablationmentioning
confidence: 99%